2005
DOI: 10.1038/sj.jea.7500448
|View full text |Cite
|
Sign up to set email alerts
|

Prostate cancer in US Air Force veterans of the Vietnam war

Abstract: US Air Force veterans of Operation Ranch Hand sprayed herbicides contaminated with 2, 3,7,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
32
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 38 publications
1
32
0
Order By: Relevance
“…For Ranch Hand veterans there is a significant 50% reduction in total cancers at the highest dioxin body burden levels compared to low-level background body burden (Kayajanian, 2001). These results are consistent with the failure to detect prostate cancer increase of the Ranch Hand group vis-à-vis Comparisons in association with either monitored TCDD levels or time served in Southeast Asia (Pavuk et al, 2006). The latter study suggested that a longer service in the Southeast Asia environment and exposures other than TCDD may have increased the risk of prostate cancer in Comparison veterans.…”
Section: Hormetic Herbicides: Dioxin and Phosfonsupporting
confidence: 71%
“…For Ranch Hand veterans there is a significant 50% reduction in total cancers at the highest dioxin body burden levels compared to low-level background body burden (Kayajanian, 2001). These results are consistent with the failure to detect prostate cancer increase of the Ranch Hand group vis-à-vis Comparisons in association with either monitored TCDD levels or time served in Southeast Asia (Pavuk et al, 2006). The latter study suggested that a longer service in the Southeast Asia environment and exposures other than TCDD may have increased the risk of prostate cancer in Comparison veterans.…”
Section: Hormetic Herbicides: Dioxin and Phosfonsupporting
confidence: 71%
“…The investigators compared serum TCDD levels and observed no increased incidence of prostate cancer among Operation Ranch Hand pilots compared with a similar cohort of Air Force veterans who served in Southeast Asia who did not spray Agent Orange. 9 That study, although it was very complete, was limited by the young age of the cohort and the institution of PSA screening in 1997. The influence of introducing PSA screening lead to a large increase in incidence of prostate cancer in the final years of observation (1999-2003), as expected.…”
Section: Discussionmentioning
confidence: 99%
“…Although there is sufficient evidence linking soft tissue sarcomas, Hodgkin disease, and non-Hodgkin lymphoma with Agent Orange exposure, 4 evidence of the risk of subsequent prostate cancer has been much less robust. [5][6][7][8][9][10] Operation Ranch Hands, a longitudinal study that was conducted on Air Force veterans, identified no increased incidence of prostate cancer compared with a similar cohort of veterans. However, that study did observe an increased risk compared with the standard US population of white men.…”
mentioning
confidence: 99%
“…Recent studies on the relationship between Agent Orange and prostate cancer have focused on US veterans of the Vietnam War (Ketchum NS et al 1998;Zafar MB et al 2001;Akhtar FZ et al 2004;Giri VN et al 2004;Justine L et al 2006;Pavuk M et al 2006;Chamie K et al 2008). However, only one study has focused on the relationship between PSA and Agent Orange in Vietnamese men (Sun XL et al 2013).…”
Section: Introductionmentioning
confidence: 99%